Clinical Outcome of CT-Guided Iodine-125 Radioactive Seed Implantation for Intrahepatic Recurrent Hepatocellular Carcinoma: A Retrospective, Multicenter Study - Yuan, Qianqian; Ma, Yanli; Wu, Linlin; Song, Yuqing; He, Chuang; Huang, Xuequan; Yang, Chongshuang; Liu, Bin; Han, Hongmei; Zhang, Kaixian; Wang, Junjie (Frontiers in Oncology, 2022)
The efficacy and safety of CT-Guided Iodine-125 Radioactive Seed Implantation (RSI) for the treatment of intrahepatic recurrent hepatocellular carcinoma (rHCC) were analyzed in this multicenter retrospective study. We reviewed the medical records of patients with rHCC treated with I-125 seed implantation at four different hospitals in China from December 2011 and January 2021. The local progression-free survival (LPFS),liver PFS, and overall survival (OS) were calculated, and the short-term efficacy and treatment-related toxicities were evaluated. A total of 82 patients were enrolled; the median follow-up time was 46 months (range, 3–80 months). The 1-, 3- and 5-year LPFS rates were 63.8%, 27.1%, and 7.9%, respectively, and the corresponding OS rates were 74.8%, 32.9%, and 12.6%, respectively. Univariate analysis showed that factors influencing LPFS included the maximum lesion diameter, Barcelona Clinic Liver Cancer (BCLC) stage, interval between treatment and recurrence, and D90. Multivariate analyses revealed that the BCLC stage, interval between treatment and recurrence, and D90 were independent factors influencing LPFS, whereas BCLC stage, D90, and short-term efficacy were independent factors influencing OS. In summary, I-125 seed implantation is a safe and effective treatment for rHCC. The BCLC stage, interval, and D90 were found to influence the local control. A larger, prospective study is required to confirm the dose-response curve for Iodine-125 RSI of rHCC.